Interactions between restorative dentistry and periodontics: luting post nonmetallic (Part II) - Bandéca, Matheus Coelho; Pinto, Shelon Cristina Souza; Tonetto, Mateus Rodrigues [UNESP]; Frizzera, Fausto [UNESP]; Pereira, Kamila Figueiredo UNESP]; Borges, Alvaro Henrique; Saad, José Roberto Cury [UNESP]; Santos, Reidson Stanley Soares (Jaypee Brothers Medical Publishing, 2014)
Endodontically treated teeth have necessary use of intracanal posts. Due to the constant need and search for esthetic materials with properties similar to tooth structure remaining fi berglass posts esthetic came good these shortcomings and are increasingly used as a fi rst option for prosthetic rehabilitation. In this case report is described step by step how to perform the cementation of a nonmetallic post and core construction for making a piece prosthetic onlay in a simplifi ed way, by choosing the self-etching cementation technique.
Keywords: Restorative dentistry; Fiber post; Luting agents